Role of neurosonography in neonates with clinically suspected intracranial pathology - Gahlot, Abhishek; Joshi, Anil (International Journal of Research in Medical Sciences, 2019)
Background: Preterm neonates have a higher mortality and morbidity because of their greater risk for intracranial hemorrhage (ICH), hypoxic ischemic encephalopathy(HIE) which can lead to poor neurodevelopmental outcomes. The present study was conducted to evaluate neonates with clinically suspected intracranial pathology by neurosonography. Methods: Included neonates were those with clinically suspected intracranial pathology admitted to neonatal intensive care unit of the Bharati Vidyapeeth Medical College and Hospital (Deemed to be University), Sangli from October 2018 till December 2018. First cranial neurosonography was done between first and third day, second between 7th and 10th day of birth. HIE also known as Periventricular leukomalacia (PVL) grading was done using the De Varies et al, grading. Severity of ICH was graded according to Papile and Burstein classification(1978). Results: Of the total 60 neonates, 61.7% were preterm and rest at term. Mean APGAR score at 1 minute was 8.6 (range 5 to 10) and at 5 minutes was 9.58 (range 8 to 10). Mean ventricular index at the first assessment was 26.78% and 26.89% at the second assessment. Grade 1 HIE was found in 17 neonates on first assessment, and two had grade 2 HIE. Second assessment revealed grade 1 HIE in 20 neonates and grade 2 in two. First assessment revealed two neonates with grade 1 and grade 2 ICH, out of which one grade 2 ICH worsened to grade 3. Two neonates were found to have corpus callosal agenesis. Conclusions: Transcranial neurosonography stands as an excellent and reliable investigation of choice for neonates to detect HIE,ICH and intracranial congenital anomalies.